LITERASI MEDIA DENGAN MEMBERDAYAKAN KEARIFAN LOKAL - SIHABUDIN, AHMAD (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2013)
Media literacy is always related to media education. The problem is why is media to perform literacy? It is because our society is heterogeneous; in terms of their ethnicity, religion, infrastructure, education, knowledge, professional background, geography and other factors. This diversity indicator results also in differences of social perspective in grasping each content of media (Potter, 2001). The printing culture drives out the society’s competence to have contact with outside of both their selfness and their collective selfness. It might be helpful as outside information that can be used to repair the life order and structure. Unfortunately, although the importance of cultural literacy is in a consideration, the level of literacy competence of our society is still low. The society is in favor of information being read. The phenomenon in Ignas Kleden’s term is so-called as the secondary orality. Values and norms of local cultures within society can be utilized as the principle guidance for them to access information from new (foreign) media. We should put efforts on how our local wisdom functions as the community filter for media contents. Research and Development Division of Kompas (2011) reports culture is one of the devices through which we can develop a media literate society. This implementation is found in the Samin community at Pati Central Java, through their solid local doctrines they are successful to defend themselves not to imitate behaviors that they are in contact with.